2012
DOI: 10.1371/journal.pone.0052525
|View full text |Cite
|
Sign up to set email alerts
|

Tuberal Hypothalamic Neurons Secreting the Satiety Molecule Nesfatin-1 Are Critically Involved in Paradoxical (REM) Sleep Homeostasis

Abstract: The recently discovered Nesfatin-1 plays a role in appetite regulation as a satiety factor through hypothalamic leptin-independent mechanisms. Nesfatin-1 is co-expressed with Melanin-Concentrating Hormone (MCH) in neurons from the tuberal hypothalamic area (THA) which are recruited during sleep states, especially paradoxical sleep (PS). To help decipher the contribution of this contingent of THA neurons to sleep regulatory mechanisms, we thus investigated in rats whether the co-factor Nesfatin-1 is also endowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 67 publications
1
21
0
3
Order By: Relevance
“…Additionally, the infusion of Nesfatin-1 antiserum after a selective PS deprivation, designed for elevating PS needs, severely prevented the ensuing expected PS recovery (Jego et al, 2012). Strengthening these pharmacological data, Jego et al (2012) finally demonstrated by using c-Fos as an index of neuronal activation that the recruitment of Nesfatin-1-immunoreactive neurons within THA is positively correlated to PS but not to SWS amounts experienced by rats prior to sacrifice. In conclusion, this work supports a functional contribution of the Nesfatin-1 signaling, operated by THA neurons, to PS regulatory mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, the infusion of Nesfatin-1 antiserum after a selective PS deprivation, designed for elevating PS needs, severely prevented the ensuing expected PS recovery (Jego et al, 2012). Strengthening these pharmacological data, Jego et al (2012) finally demonstrated by using c-Fos as an index of neuronal activation that the recruitment of Nesfatin-1-immunoreactive neurons within THA is positively correlated to PS but not to SWS amounts experienced by rats prior to sacrifice. In conclusion, this work supports a functional contribution of the Nesfatin-1 signaling, operated by THA neurons, to PS regulatory mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Nesfatin-1 is co-expressed with MelaninConcentrating Hormone (MCH) in neurons from the tuberal hypothalamic area (THA) which are recruited during sleep states, especially paradoxical sleep (PS) (Jego et al, 2012). To help decipher the contribution of this contingent of THA neurons to sleep regulatory mechanisms, Jego et al (2012) thus investigated in rats whether the co-factor Nesfatin-1 is also endowed with sleepmodulating properties.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations